TO STUDY THE IMPACT OF THE CHANGING SOCIAL AND CULTURAL ENVIRONMENT OF MODERN INDIA ON THE MORAL VALUES ​​OF STUDENTS - Rustagi, Kavita; Parveen, Nahid (ShodhKosh: Journal of Visual and Performing Arts, 2024)
India has been the bearer of an ancient civilization, the foundation of which rests on moral values ​​and spiritual ideas. For centuries, this country has been known for its education system with high moral values, but in the last few decades, a rapid change has been observed in the educational sector and the lives of students in India, which is the result of the influence of western culture, modernization, globalization and technological advancement, due to which the moral values ​​of their lives are getting affected. Today in the 21st century, the traditional concepts of education are changing due to the increasing influence of high information technology. At present, the problem of disappearance of moral values ​​in the lives of students is becoming fully visible. The continuous decline in moral values ​​like humility, truthfulness, virtue, love, benevolence, discipline, tolerance and non-violence in the lives of students is a matter of concern. Therefore, it is very timely to do an in-depth study on this subject. To solve this problem and revive moral education, the Government of India has created the ’National Education Policy 2020’, which is based on the Indian knowledge tradition and has imbibed Indian cultural values, beliefs, ideals and requirements in the field of education. ’National Education Policy 2020’ is committed to improving all the weak aspects of modern education and restructuring moral education.